2009
DOI: 10.1111/j.1365-2923.2009.03416.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-method analysis of free-text comments from the UK General Medical Council Colleague Questionnaires

Abstract: There is an inevitable trade-off between the capturing of indicators of problematic performance (i.e. adverse statements which contradict a positive scale rating) and the ease with which such statements can be identified. Our data suggest there is little benefit in routinely analysing narrative comments for the purposes of revalidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 11 publications
(27 reference statements)
2
39
1
Order By: Relevance
“…This finding aligns with a UK study of free-text comments from faculty on colleagues' overall performances, which reported that higher mean scores correlated with a greater number of positive comments. 24 Research on assessments of medical students 22 and trainee doctors 25 showed similar patterns.…”
Section: Explanations For and Interpretations Of Findingsmentioning
confidence: 66%
“…This finding aligns with a UK study of free-text comments from faculty on colleagues' overall performances, which reported that higher mean scores correlated with a greater number of positive comments. 24 Research on assessments of medical students 22 and trainee doctors 25 showed similar patterns.…”
Section: Explanations For and Interpretations Of Findingsmentioning
confidence: 66%
“…Such analyses of comments within quantitative surveys has been previously used to research health service issues. 32 The first stage of the analysis sought to discover the different ways that participants chose to answer the freetext question and develop a representative thematic framework. After careful reading and data immersion, 33 one researcher (RW) conducted a conventional qualitative content analysis, 34 coding all comments and identifying broad themes within an initial framework.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analysts inductively coded the open-text feedback from the GMC-CQ into 5 themes relating to (1) innovation and openness to change (59/1636 comments, 3.6%); (2) interpersonal skills and caring (432/1636 comments, 26.4%); (3) popularity (131/1636 comments, 8%); (4) professionalism (701/1636 comments, 42.8%); and (5) respect or esteem in which the doctor was held (346/1636 comments, 21.1%) [12]. We refer to these categories throughout the rest of the paper as innovator, interpersonal skills, popularity, professionalism, and respect.…”
Section: Methodsmentioning
confidence: 99%
“…Although doctors’ performance might be best assessed by fellow professionals who know them very well, positive reporting bias in open-text reports may occlude differences in performance [11,12]. The challenge therefore is to classify differences in text that is often positively worded and to use these classifications to signal differences in doctors’ performance.…”
Section: Introductionmentioning
confidence: 99%